2008
DOI: 10.1021/cm703616q
|View full text |Cite
|
Sign up to set email alerts
|

Improved Thermoelectric Performance in Yb14Mn1−xZnxSb11 by the Reduction of Spin-Disorder Scattering

Abstract: Rare-earth transition metal compounds Yb 14 Mn 1-x Zn x Sb 11 , isostructural with Ca 14 AlSb 11 , have been prepared using a metal flux growth technique for thermoelectric property measurements (with x ) 0.0, 0.2, 0.3, 0.4, 0.7, 0.9, and 1.0). Single-crystal X-ray diffraction and electron microprobe analysis data indicate the successful synthesis of a solid-solution for the Yb 14 Mn 1-x Zn x Sb 11 structure type for 0< x < 0.4. Hot-pressed polycrystalline samples showed that the product from the flux reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 27 publications
4
114
0
Order By: Relevance
“…While Ce was only observed on the Yb(2) site for x = 0.32, samples with x = 0.45 and higher show Ce both on the Yb (2) and Yb (4) volume followed by Yb(4), while Yb(1) and Yb(3) have the smallest volumes. 24 Previous work on Eu 13 AMnSb 11 showed that smaller ions such as Ca and Yb prefer to substitute on the Eu(3) and Eu(1) sites while larger ions such as Ba and Sr prefer to substitute on the Eu(2) and Eu(4) sites, 25 respectively, consistent with the Hirshfeld analysis. Since Ce 3+ is similar in size to Yb 2+ , it is surprising that it has such a strong preference for the Yb(2) and Yb (4) Temperature-dependent molar susceptibility data from single crystals with x = 0-0.58 are shown in Figure 3(a) in the temperature range where ferromagnetic ordering is observed.…”
Section: +supporting
confidence: 61%
“…While Ce was only observed on the Yb(2) site for x = 0.32, samples with x = 0.45 and higher show Ce both on the Yb (2) and Yb (4) volume followed by Yb(4), while Yb(1) and Yb(3) have the smallest volumes. 24 Previous work on Eu 13 AMnSb 11 showed that smaller ions such as Ca and Yb prefer to substitute on the Eu(3) and Eu(1) sites while larger ions such as Ba and Sr prefer to substitute on the Eu(2) and Eu(4) sites, 25 respectively, consistent with the Hirshfeld analysis. Since Ce 3+ is similar in size to Yb 2+ , it is surprising that it has such a strong preference for the Yb(2) and Yb (4) Temperature-dependent molar susceptibility data from single crystals with x = 0-0.58 are shown in Figure 3(a) in the temperature range where ferromagnetic ordering is observed.…”
Section: +supporting
confidence: 61%
“…13 Inspired by our previous investigation of the thermoelectric properties of Zn-doped Yb 14 MnSb 11 , here we consider Ca 5 Al 2Àx Zn x Sb 6 (x ¼ 0, 0.02, 0.05, 0.10, and 0.20). 17 Zn is an attractive dopant due to its low cost and ease of handling. A combination of high temperature transport measurements and classic transport theory is used to compare the effects of Na-and Zn-doping in Ca 5 Al 2 Sb 6 .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 They oen have very low lattice thermal conductivity due to their large unit cells, and it is possible to nely tune their electronic properties by doping, providing a route to improved zT. High thermoelectric efficiency has been demonstrated in a number of different Zintl compounds [7][8][9][10][11][12][13][14][15][16][17] including Yb 14 MnSb 11 (ref. 16 and 18) and YbCd 2Àx Zn x Sb 2 , both of which have zT values above unity at high temperatures.…”
Section: Introductionmentioning
confidence: 99%